ILLOCUTIONARY ACT FOUND IN JUST ALVIN TALK SHOW ON METRO TV“CINTA UNTUK AINUN” - AMIRO, RISHA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : Illocutionary Acts, Talk show. Speech act is action perform via utterance. Speech act does not only occurin daily life, it can also occur in a television program like in a talk show program.In this research the writer used Just Alvin talk show program as the object to findlocutionary and illocutionary acts used by the presenter and also the guest stars.The research questions are focused on two answer namely the locutionary andillocutionary acts based on the theory of Levinson and Searle. This research used descriptive qualitative method. The data were explained and analyzed using speech act theory.After finding the locutionary and illocutionary act in Just Alvin talk show,the types of locutionary act can be described as follows: declarative, imperativeand interrogative. The most frequent of the locutionary acts  performed  isdeclarative. Meanwhile, the types of illocutionary act can be described as follows:first, most speakers use representatives to represent a statement. Second, thespeakers use dirrectives to command or request some one to do an action. Third, the speakers use commisives to commit him or herself to the  performance of action. Fourth, the speakers use expressives type to express the psychological condition about the situation or state, like pleasure or sadness. Meanwhile, the declaration type is not found in this research. It is hoped that this research contributes important information for the next researcher who is interested in doing the same kind of study. It is suggested for further researchers to use another theory of illocutionary acts, so that different results might be found. Moreover, they can analyze another objects which might contain declaration illocutionary act.